There will be blood: crime rates in shale-rich U.S. - James, A (University of Oxford, 2014)
Over the past decade, the production of shale oil and gas signicantly increased in the United States. This paper uniquely examines how this energy boom has aected regional crime rates throught the United States. There is evidence that, as a result of the ongoing shale-energy boom, shale-rich counties experienced faster growth in rates of both property and violent crimes including rape, assault, murder, robbery, burglary, larceny and grand-theft auto. These results are particularly robust for rates of assault, and less so for other types of crimes. Policy makers should anticipate these effects and invest in public infrastructure accordingly.